Electrochemical investigation on hierarchical sea urchin shaped zinc nickel selenide for efficient supercapacitor. Issue 19 (1st October 2022) - Priyadharshini, M.; Pazhanivel, T.; Maiyalagan, T.; Albaqami, Munirah D.; Ganesh, P.S.
Abstract: Fabrication of efficient electrode material i.e., with better electrochemical behaviour and high cycling stability is a major issue in the area of supercapacitors. Herein, we report the synthesis of nickel zinc selenide through hydrothermal method followed by a calcination process. The systematic investigation have been carried out to analyse the structure and electrochemical properties. Ex-situ microscope pictures affirms the sea urchin morphology of MOF derived Ni/ZnSe. Electrochemical analysis exhibited a maximum specific capacitance of 870 Fg -1 at 5 mVs -1 . Homogeneous distribution of sea urchin morphology displays a high capacitance, rate capability and cyclability because of rigid structure and high specific surface area(SSA) enhancing facile ionic interaction. Hence this work proposes an idea for advanced electrode materials for efficient supercapacitors. Graphical abstract: Image 1